Whole-Genome Sequencing for Investigation of Possible Hospital Transmission of Tuberculosis. (October 2020) - Rasmusson, Jenna; Sampathkumar, Priya; Wengenack, Nancy
Abstract : Background: Whole-genome sequencing (WGS) is increasingly used in epidemiological investigations of infectious diseases. We describe the use of WGS to identify drug-resistance variants of tuberculosis (TB) and to determine potential transmission between patients at an academic medical center. Methods: Chart review and interviews of patients and healthcare workers along with WGS of M. tuberculosis isolates from the patients. Clinical information: In June 2019, patient A, a 20-year-old college student born in the United States was admitted with massive hemoptysis. The patient was identified as having active, cavitary TB that was acid-fast smear positive, and the mycobacterial culture grew M. tuberculosis . Patient B, a 40-year-old foreign-born patient with advanced lung cancer was acid-fast smear negative, but mycobacterial cultures were positive for M. tuberculosis . The 2 patients had overlapping stays in the medical intensive care unit. There was concern that patient B had acquired TB during her stay in the hospital from patient A, who was highly infectious. WGS showed that the mycobacterial isolates from the 2 patients were unrelated. Patient A was a student at a college campus where the state health department had previously issued a health advisory concerning active pulmonary TB in a student; and 7 additional TB cases were subsequently identified through contact investigation. Patient A denied any contact with other persons who were part of the outbreak and had not been included in the contact investigations of any of the cases. Of the 8 outbreak cases, 6 had been seen at our institution and had isolates available for testing. WGS showed that these 6 isolates matched patient A, establishing that she was part of the college outbreak. Conclusions: WGS was useful in establishing the source of M. tuberculosis infection in a patient who did not have known exposure to TB and in demonstrating that transmission of TB did not occur in the hospital. Funding: None Disclosures: None